Immobilization of resin photocatalyst in removal of soluble effluent organic matter and potential for disinfection by-products - E.N. Hidayah; R.B. Pachwarya; O.H. Cahyonugroho (Global Journal of Environmental Science and Management, 2022)
BACKGROUND AND OBJECTIVES: The existence of organic matter is one of the main issues for wastewater reclamation since chlorination is applied most frequently before use wastewater reclamation for many purposes. One of the eco-friendly and effective methods is using innovative material through resin immobilized heterogeneous photocatalyst, which is based on the principle of advanced oxidation processes.  Resin immobilized photocatalyst has been using for pollutant reduction, however lack of studies focused on dissolved effluent organic matter and its impact on the formation carcinogenic as by-product of water or wastewater treatment. This study aims to characterize organic matter by resin immobilized photocatalyzed titanium dioxide and zinc oxide and to determine its effectiveness in removing organic matter and potential for disinfection by-products in treated wastewater compare with resin only.METHODS: The bulk parameters, including total organic carbon, aromatic organic carbon as ultraviolet at 254 nm wavelength and specific ultraviolet absorbance value, and disinfection by-products formation potential, including trihalomethanes and haloacetic acids concentration was measured.FINDINGS: The results present that all materials could remove organic carbon in the range 58.18% - 93.45%, aromatic organic carbon removal 48.77% - 76.51%, and specific ultraviolet absorbance value decreased into less than 2 L/mg-m after longer contact time. Disinfection by-products formation potential concentration removal decreased and indicated the consistency results with bulk parameters removal. Resin immobilized photocatalyzed zinc oxide performed a higher efficiency removal than resin immobilized photocatalyzed titanium dioxide and resin only.CONCLUSION: This study exhibited the performance of resin immobilized photocatalyst with titanium dioxide and zinc oxide in removing dissolved organic matter and to control the formation of disinfection by-products. A combination between bulk parameters and disinfection by-products formation potential removal concluded that the aromatic structure, was mainly haloacetic acids precursors, while the non-aromatic organic fraction was probably trihalomethanes precursors.